Adapter les mesures préventives de santé et de sécurité pour les travailleurs qui cumulent des précarités : les obligations d’équité - Sylvie Gravel; Katherine Lippel; Daniel Vergara; Jessica Dubé; Jean-François Ducharme; Gabrielle Legendre (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article summarises the findings of a literature review and of consultation with experts on the health of workers who simultaneously hold precarious job situations : temporary employment agency workers, small non-unionized business workers, and temporary foreign workers. We have observed that : a) it is difficult to draw a portrait of the health of these workers because : b) they are not specifically identified within companies and receive no special attention ; c) they are often hired in non-priority sectors where rigorous monitoring is lacking ; and d) they are excluded from OHS practices because they are only temporarily employed by these companies. These conditions serve to keep them marginalised, even though it would be possible to adapt preventive, occupational health and safety (OHS) practices for workers in precarious job situations. This could be accomplished by reframing our OHS authorities’ scientific, administrative, legal, and moral obligations for social justice.